Directed Self‐Assembly of Patchy Microgels into Anisotropic Nanostructures. Issue 2 (21st January 2020) - Xu, Jianchang; Wang, Zhikun; Zhang, Fusheng; Peng, Shiyuan; Zhang, Jing; Zhang, Lijuan
Abstract : Front Cover : In article number 1900505, Lijuan Zhang and co‐workers propose a simple and versatile strategy to construct various anisotropic nanostructures through the single‐directional and multi‐directional self‐assembly of patchy microgels, which was studied using dissipative particle dynamics simulation. A general criterion of interaction parameters was developed to guide the directed self‐assembly behavior of nanoparticles.